Complete Genome Sequence of Escherichia coli 81009, a Representative of the Sequence Type 131 C1-M27 Clade with a Multidrug-Resistant Phenotype - Mutti, Michele; Sonnevend, Ágnes; Pál, Tibor; Junttila, Sini; Ekker, Heinz; Galik, Bence; Gyenesei, Attila; Nagy, Gábor; Nagy, Eszter; Szijártó, Valéria (Genome announcements (Washington, DC), 2018)
The sequence type 131 (ST131)- H 30 clone is responsible for a significant proportion of multidrug-resistant extraintestinal Escherichia coli infections. Recently, the C1-M27 clade of ST131- H 30, associated with bla CTX-M-27 , has emerged. The complete genome sequence of E. coli isolate 81009 belonging to this clone, previously used during the development of ST131-specific monoclonal antibodies, is reported here.